Proses Optimasi Produksi Bioetanol dari Limbah Serat Buah Sawit dengan Metode SHF - Edy Wibowo Kurniawan (Jurnal Loupe, 2020)
The Indonesian government is trying to equalize development including the energy sector. The government launched the use of alternative energy starting in 2008 with a blueprint for searching and utilizing new renewable energy sources in Indonesia through biofuels, one of the alternative energy developed is bioethanol. The research objective is the optimization of the SHF method bioethanol production process from palm fruit fiber waste. The experimental design uses central composite design with variable H2SO4 concentration and fermentation time. The first stage in the study was by saccharifying the palm oil fiber waste by the hydrolysis method using H2SO4 (concentrations of 1 M, 2 M, and 3 M). Then the next stage is fermentation process (fermentation time is 1 day, 2 days, 3 days, 4 days and 5 days). Sugar content analysis was carried out in the fermen solution and analysis of bioethanol levels in each running experiment. Then the optimization is done with the response surface method (RSM). Based on the research, the optimum condition of the bioethanol production process is H2SO4 concentration of 2.76 M with a fermentation time of 4.64 days which will produce bioethanol levels of 28.6027 g/L.